2012
DOI: 10.1021/bm201637e
|View full text |Cite
|
Sign up to set email alerts
|

Drastically Lowered Protein Adsorption on Microbicidal Hydrophobic/Hydrophilic Polyelectrolyte Multilayers

Abstract: Polyelectrolyte multilayer films assembled from a hydrophobic N-alkylated polyethylenimine and a hydrophilic polyacrylate were discovered to exhibit strong antifouling, as well as antimicrobial, activities. Surfaces coated with these layer-by-layer (LbL) films, which range from 6 to 10 bilayers (up to 45 nm in thickness), adsorbed up to 20 times less protein from blood plasma than the uncoated controls. The dependence of the antifouling activity on the nature of the polycation, as well as on assembly condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 65 publications
1
68
2
1
Order By: Relevance
“…These results suggest that both peptides likely adopt a disordered, random configuration on the Au surface. [43][44] A similar result was also observed previously with an EKEKEKE-C peptide. 34 In addition to the secondary structure, the zeta potentials of the CRERERE peptide were also measured at different pH values to confirm its zwitterionic property.…”
Section: Resultssupporting
confidence: 88%
“…These results suggest that both peptides likely adopt a disordered, random configuration on the Au surface. [43][44] A similar result was also observed previously with an EKEKEKE-C peptide. 34 In addition to the secondary structure, the zeta potentials of the CRERERE peptide were also measured at different pH values to confirm its zwitterionic property.…”
Section: Resultssupporting
confidence: 88%
“…Investigations into tuning of proteolytic susceptibility have shown that although some human proteases have poor activity against LbL films (63), film characteristics including covalent cross-linking (64), L-or D-polypeptides (65), and terminal layer charge (66), among others, can enhance or inhibit degradation. In addition, antifouling modifications like PEGylation (67) and mixed-charge nanodomains (68) can introduce a protein resistance that reduces enzyme contact with the film. This versatility in LbL-assembled films, coupled with the nonenzymatic hydrolytic release mechanism, can readily accommodate a variety of modifications that specifically tune film characteristics to the desired application.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Wong and coworkers showed that the protein adsorption is drastically lowered on microbicidal hydrophobic/hydrophilic polyelectrolyte multilayers. [18] It was shown recently [19] that that the extent of adhered bacteria mostly depends on the type of terminating polyelectrolyte layer, although surface roughness and hydrophobicity should be also taken into account.…”
Section: Introductionmentioning
confidence: 99%